Analisis Wacana Kritis Monolog Dalam Talk Show Mata Najwa Edisi "Menanti Terawan" - Lailiyah, Nur; Kurwidaria, Favorita; Indri W, Farida; Sumarlam, Sumarlam (Efektor, 2021)
This study aims to analyze the elements of text, interpretation, and explanation using a critical discourse analysis approach. The textual strategy focuses on choosing the right vocabulary and the use of certain grammar. The method used is the watch-free-to-talk (SBLC) method with the note-taking technique. This type of qualitative descriptive research, while the data analysis technique is carried out by referring to the framework of Fairclough's discourse analysis dimensions, namely: text analysis, namely descriptions, interpretations, and explanations that will be used as techniques in data analysis. The results obtained are as follows: first, the types of sentences used include directive, interrogative and imperative which are also strategies for text producers to show their ideology, as well as indirect assessments of participants. Second, the vocabulary used has the purpose of emphasizing, and obscuring the real meaning. In addition to the vocabulary, the textual analysis also includes grammatical aspects by utilizing transitivity, positive-negative sentences, and modalities, as well as utilizing textual structures that are in accordance with the inverted pyramid using the news text construction pattern. So that in the socio-cultural dimension there are changes in situations, changes in institutions, and social changes.